The Application of Levine’s and Kolcaba’s Theories in the Nursing Care of Patients with the Third Stadium of Cervical Cancer - Ingrit, Belet Lydia (IJNP (Indonesian Journal of Nursing Practices), 2019)
Background: Cervical cancer was the second leading cause of cancer in Indonesia. New cases of cervical cancer are found in Indonesia each year.Objective: This study aims to describe an application of Levine’s Conservation Nursing Theory and Kolcaba’s Comfort Theory in a patient with the third stadium of cervical cancer.Method: The method used in this study was a narrative of a case report in one patient with the third stadium of cervical cancer at the hospital in Central Jakarta. She is 44 years old, who has been diagnosed since October 2017. She experienced nausea and vomiting a week before she was hospitalized and had a history of vaginal discharge ever since nine months ago. Levine’s conservation interventions were provided to maintain energy, improve adaptability, improve standard comfort, educate, and provide comfort.Results: The result showed that the patient was able to adapt to the condition of the illness and obtained a sense of comfort during hospitalization. Therefore, Levin's conservation theory and Kolcaba's comfort theory can be applied in performing nursing care in patients with cervical cancer.Conclusion: The three stages of Kolkaba's comfort intervention can improve patient comfort not only physically but also psychologically during treatment.